What type of crisis is this? The coronavirus crisis as a crisis of the economicised society - Walter Ötsch (Cusanus Hochschule für Gesellschaftsgestaltung, Institute für Ökonomie und für Philosophie, 2020)
The paper addresses the following questions: what type of crisis is this? How can we put the events together in our minds so that we have a coherent, complete picture of the crisis? How can we put this crisis in its historical context and what are the consequences for the future of our society? The paper consists of three parts: (1) a background to the crisis, esp. economic facts, (2) an interpretation of the crisis and (3) an outlook to the future and potential scenarios for how society will react to the crisis.
Keywords: A11; B25; E65; F02; F60; H10; I18; N01; P16; Z13; 330; Corona crisis; scenarions; society; Neoliberalism; market fundamentalism